The heat flow, thermal history of the oil source Lower Jurassic Togurskaya suite and oil-and-gas potential of the Paleozoic of the Koltogor mezodepression(southern segment of the Koltogor-Urengoy paleorift) - G. A. Lobova; T. E. Luneva; V. I. Isaev; A. N. Fomin; Ju. V. Korzhov; M. F. Galieva; D. S. Krutenko (Геофизический журнал, 2019)
Input of the pre-Jurassic («Paleozoic») oil is important to the reproduction of the in-situ resources base of Western Siberian oil and gas extraction. Prospecting and forecasting studies of the pre-Jurassic reservoirs in the territory of the Koltogor mezodepression and structures of its surrounding — in the north-western part of Tomsk Region, in the zone of the southern segment of the Koltogor-Urengoy Permian-Triassic paleorift are of interest. The pre-Jurassic oil and gas complex(oil and gas bearing horizon of the contact zone— OGBHCZ and, actually, the Inner Paleozoic) is assigned along with the Cretaceous (the Neocomian), Upper Jurassic, Middle Jurassic and Lower Jurassic oil and gas complexes in the study area. It is accepted that the Upper Jurassic Bazhenov suite is the oil source formation for the Middle Jurassic, Upper Jurassic and Cretaceous oil and gas complexes, as well as Togurskaya suite — for the Lower Jurassic and pre-Jurassic deposits. Researches are carried out in the context of the methodology of the sedimentary and migrational theory of naftidogenesis. Spatiotemporal localization of the generation foci of Togurskaya oil is performed with the original method of paleotemperature modeling. The heat flow in sections of 82 deep wells is calculated at the first stage of modeling. At the following stages the oil source suite geotemperatures are directly figured up in key moments of geological time. The integral express-assessment of realization of generation potential of the suite is performed on the base of calculated data about time of the oil source suite residence in the main oil generation zone and its geotemperatures. Vewing to the concept about predominantly vertical migration of hydrocarbons the forecasting is carried out in the outline of the oil source suite distribution. Schemes of distribution of Togurskaya oil accumulation density are built and zoning of deposits is performed taking into account the thickness and quality of potential reservoirs of the pre-Jurassic deposits. Oil geological zoning of the pre-Jurassic complex and ranking areas according to the degree of prospect abilities were accomplished. The most forward-looking zone for prospecting in the weathering crust reservoir is the area, which comprises the eastern part of the Cheremshanskaya mezzo saddle and its articulation with the northern side of the Koltogor mezodepression and the western slope of the Srednevasyuganskiy megaswell (in the order of 3500 km2). The most optimistic forecast for the Inner Paleozoic reservoir is made for the same areas as for the weathering crust, less optimistic — for the Severo-Chkalovskiy incised valley and its articulation with the Murasovskiyhigh and Trassovoe dome-shaped uplift (in the order of 5700 km2).Consistency of the forecast with established direct evidence of oil saturation amounts to 70 %. Detailed map of the heat flow density in the study area showed that the trench of the Koltogor-Urengoy graben-rift does not have significant manifestation in enhanced values of the heat flow. The article demonstrates methodological approaches and complex technology of zonal forecasting of oil and gas potential of the pre-Jurassic basement of Western Siberia, which are working out by Tomsk research school of Geothermy.